2019
DOI: 10.1371/journal.pone.0224339
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of leisure-time sedentary behavior among 181,793 adolescents aged 12-15 years from 66 low- and middle-income countries

Abstract: BackgroundSedentary behavior is a growing public health concern in young adolescents from low- and middle-income countries (LMICs). However, a paucity of multinational studies, particularly in LMICs, have investigated correlates of leisure-time sedentary behavior (LTSB) in young adolescents. In the current study, we assessed socio-demographic, socio-economic, socio-cultural and health behavior related correlates of LTSB among adolescents aged 12–15 years who participated in the Global school-based Student Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 43 publications
3
23
1
1
Order By: Relevance
“…Finally, physical inactivity was a risky health behavior found in each of the profiles observed. A known and common problem in most low- or moderate-income countries, especially in Africa [ 61 ], as several studies have previously shown, is the existence of associations between a sedentary lifestyle and suicidality [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, physical inactivity was a risky health behavior found in each of the profiles observed. A known and common problem in most low- or moderate-income countries, especially in Africa [ 61 ], as several studies have previously shown, is the existence of associations between a sedentary lifestyle and suicidality [ 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the distribution of physical activity is analyzed within a particular country (i.e., not between countries), based on the GSHS conducted from 2009 to 2016, Vancampfort et al found that adolescents from poor families were less likely to meet the recommended sufficient physical activity [ 39 ].This question was not assessed in the present study, as we did not have socio-economic indicators at the individual level for all students included in this study. However, it is known, for example, that students from families with high socio-economic status are more likely to attend gym memberships and to live in a favorable environment, like an area with green areas, sports facilities, bike trails, and adequately connected streets [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A review of 130 surveillance studies showed ≥50% of children and adolescents engaged in sedentary behavior for ≥2 h/day in recent years [ 11 ]. Based on the GSHS in 2006–2016, it was estimated that 26.4% of adolescents had sedentary behavior for ≥3 h/day during their leisure time [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol and substance use has been observed to have the combined effects of complicating the course of depression and impairing judgement of a person experiencing depression, and at the same time resulting in high impulsivity which leads to acute life-threatening behaviours such as attempted suicide [51]. Leisure-time sedentary behaviour is now a common problem across most lowand middle-income countries, including those in Africa [52]. As a risk factor, leisure-time sedentary behaviour is associated with elevated levels of depressive symptoms, which in turn increases that risk for suicidal behaviour among young people [43,53].…”
Section: Factors Associated With Suicidal Behavioursmentioning
confidence: 99%